2002
DOI: 10.1103/physrevb.66.041104
|View full text |Cite
|
Sign up to set email alerts
|

Non-Fermi liquid behavior and scaling of the low-frequency suppression in the optical conductivity spectra ofCaRuO3

Abstract: Optical conductivity spectra σ1(ω) of paramagnetic CaRuO3 are investigated at various temperatures. At T = 10 K, it shows a non-Fermi liquid behavior of σ1(ω) ∼ 1/ω 1 2 , similar to the case of a ferromagnet SrRuO3. As the temperature (T ) is increased, on the other hand, σ1(ω) in the low frequency region is progressively suppressed, deviating from the 1/ω 1 2 -dependence. Interestingly, the suppression of σ1(ω) is found to scale with ω/T at all temperatures. The origin of the ω/T scaling behavior coupled with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
62
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 24 publications
(37 reference statements)
9
62
1
Order By: Relevance
“…The non-Fermi-liquid self energy we find bears an intriguing resemblance to the self energy inferred from optical conductivity measurements on SrRuO 3 [19,20,21].…”
supporting
confidence: 71%
“…The non-Fermi-liquid self energy we find bears an intriguing resemblance to the self energy inferred from optical conductivity measurements on SrRuO 3 [19,20,21].…”
supporting
confidence: 71%
“…2) exhibits metallic resistivity with a non-Fermi-liquid temperature dependence best described by a sub-linear form in its hightemperature range above 60 K, ρ(T ) ∝ T α with α = 0.74, in qualitative agreement with prior work that had yielded powerlaw exponents α = 1/2 and 3/2 for the high-and lowtemperature ranges, respectively. [8][9][10][11] This has been ascribed to the influence of spin fluctuations in proximity to a ferromagnetic quantum critical point. The resistivity of the CaMnO 3 film exhibits insulating, activated behavior (Fig.…”
Section: A DC Transportmentioning
confidence: 99%
“…[8][9][10][11] and CaMnO 3 (Refs. [12][13][14][15] and show that a comparison between far-infrared and dc-MR measurements can yield insights into the origin of this behavior.…”
Section: Introductionmentioning
confidence: 99%
“…It is in fact observed that in a large number of bad metals the Drude peak in the optical conductivity moves away from ω = 0 as the temperature is increased, leading to a suppression of low frequency spectral weight. This phenomenon is seen in ruthenates [16,17], cobaltates [18,19], cuprates [20][21][22][23][24], vanadates [25,26], manganates [27,28], nickelates [29] and organic conductors [30,31]. The behavior is illustrated in figure 1 below.…”
mentioning
confidence: 92%